2022
DOI: 10.1038/s41467-022-34427-x
|View full text |Cite
|
Sign up to set email alerts
|

Translation regulatory factor BZW1 regulates preimplantation embryo development and compaction by restricting global non-AUG Initiation

Abstract: Protein synthesis is an essential step in gene expression during the development of mammalian preimplantation embryos. This is a complex and highly regulated process. The accuracy of the translation initiation codon is important in various gene expression programs. However, the mechanisms that regulate AUG and non-AUG codon initiation in early embryos remain poorly understood. BZW1 is a key factor in determining the mRNA translation start codon. Here, we show that BZW1 is essential for early embryonic developm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 56 publications
0
2
0
Order By: Relevance
“…Abnormal expression of this gene is associated with a variety of cancers [ 61 , 62 ]. In addition, BZW1 , as a translation initiation regulation factor, plays an important role in preimplantation embryo protein synthesis [ 63 ]. However, its association with COPD remains to be studied.…”
Section: Discussionmentioning
confidence: 99%
“…Abnormal expression of this gene is associated with a variety of cancers [ 61 , 62 ]. In addition, BZW1 , as a translation initiation regulation factor, plays an important role in preimplantation embryo protein synthesis [ 63 ]. However, its association with COPD remains to be studied.…”
Section: Discussionmentioning
confidence: 99%
“…It was observed that before the 8-cell embryo polarization, ezrin was uniformly distributed over the entire cell surface. Once ezrin was phosphorylated, it aggregated from the cell junctions to the apical region, causing the microvilli to also aggregate in the apical region, indicating that phosphorylation of ezrin threonine-567 is necessary for the redistribution of embryo polarization ( Yildirim et al, 2021 ; Zhang et al, 2022b ). Recent studies have revealed that transcription factor AP-2 gamma (Tfap2c) and TEA domain transcription factor 4 (Tead4) can recruit ezrin proteins to localize to the membrane and promote the polarized growth of apical protein clusters, which eventually leads to apical protein centration.…”
Section: The Biological Function Of Ezrin In the Female Reproductive ...mentioning
confidence: 99%